Realization of Accurate Load Impedance Characterization for On-Wafer TRM Calibration - Su, Jiangtao; Wang, Jianhua; Wang, Fei; Sun, Lingling (Frontiers in Physics, 2021)
In this paper, the uncertainty and the impact of imperfect load calibration standard for on-wafer Through-Reflect-Match calibration method are analyzed with the help of 3D electromagnetic simulations. Based on the finding that load impedance can lead to significant errors in calibration, an automatic algorithm to determine the complex impedance of the load standard is proposed. This method evaluates the resistance as well as the parasitic inductance introduced by the misalignment of the probe tip to the substrate pad at mm-wave frequencies or the non-precize load standard. The proposed algorithm was verified by practical measurement, and the results show that by incorporating actual load impedance into the calibration algorithm, the deviations of RF measurement results are greatly suppressed.